Linguistic norms of Hong Kong English in computer-mediated communication - Poon, Wing Kin Vinton (The University of Edinburgh, 2011)
Hong Kong is widely known as a bilingual city. In addition to the locally spoken Cantonese, the vast majority of Hong Kong Chinese people are also able to speak English, the ex-colonial and the international language which has played an important role in the community since the colony was founded. This linguistic situation has given rise to a local variety of English. Recognising the distinct form and function of this variety, scholars (e.g. Bolton 2002, Joseph 2004: 132-161) have argued that the linguistic features in the English spoken by Hong Kong people should be identified as Hong Kong English (HKE). Observing that certain Hong Kong English features specific to computer-mediated communication (CMC) have been developed through communication among bilingual Hong Kong Chinese on the internet, I believe that Hong Kong English in CMC should be seen as a distinct variety. To support my argument, I have, in this thesis, re-examined the notion of linguistic variety. This in turn has required an investigation into the nature of the linguistic norms that define a 'systematically different' form of language. I begin my study by looking at the sociolinguistics of Hong Kong. The distribution of the three main languages – Cantonese, English, and Putonghua – is examined, and Cantonese-English code-mixing is discussed. The focus then turns to the notion of Hong Kong English, and its linguistic features are analysed. Then, the nature of computer-mediated communication is explored. I look at how this context has affected the use of language in general, and HKE specifically. The distinctive HKE features that can only be seen in CMC are examined. I show that Hong Kong English in computer-mediated communication (CHKE) is formally different from HKE in other written contexts. In order to argue that CHKE is a variety of its own, I look at how various scholars define 'variety' and similar notions such as 'language', 'dialect', 'sociolect', and 'register'. Seeing that the concept of norms is essential in determining whether a variety is 'systematically different', I explore the nature of social norms and linguistic norms. A model of norms is proposed, identifying three kinds of linguistic norms: formal norms, contextual norms and identity norms. I present the results of a survey I conducted that aims to elicit Hong Kong people‘s attitudes towards CHKE. Analysis of the data obtained from the survey shows that linguistic norms of CHKE have emerged. Not only is CHKE recognised by its users as a distinct variety, this variety also has an identity marking function that is not seen in other forms of written HKE.
Keywords: Hong Kong English; computer-mediated communication; linguistic norms; language and variety